Investigation, management and therapeutic outcome in 12 cases of childhood and adolescent Cushing's syndrome. - Weber, A; Trainer, P; Grossman, AB; Afshar, F; Medbak, S; Perry, L; Plowman, P; Rees, L; Besser, G; Savage, M (1995)
OBJECTIVE: Cushing's syndrome in childhood and adolescence is rare. We analysed the clinical presentation, investigation, management and therapeutic outcome in 12 paediatric patients with Cushing's syndrome. DESIGN: Retrospective review of case notes. PATIENTS: Twelve patients, 7 males and 5 females, aged 7.6-17.8 years with Cushing's syndrome who were admitted to St Bartholomew's Hospital between 1978 and 1993, were studied. Aetiologies of the Cushing's syndrome patients were: Cushing's disease (9), adrenal adenoma (1), nodular adrenocortical dysplasia (1) and ectopic ACTH syndrome (1). One further male patient, aged 17.8 years who presented with Nelson's syndrome after bilateral adrenalectomy for Cushing's disease in 1978, is described. MEASUREMENTS: Presenting symptoms, endocrine tests for hypercortisolism, imaging studies, simultaneous bilateral inferior petrosal sinus sampling and therapeutic strategies are discussed. RESULTS: The dominant clinical features were obesity, short stature, virilization, headaches, fatigue and emotional lability. Investigations confirmed Cushing's syndrome by demonstrating absent cortisol circadian rhythm and impaired suppression on low dose dexamethasone test and differentiated Cushing's disease from other aetiologies by high dose dexamethasone and hCRH tests. In Cushing's disease, pituitary CT scan identified a microadenoma in 4 out of 9 subjects. In 5 of the 9 patients (3 with a normal pituitary CT, 2 with a suggested microadenoma), a pituitary MRI scan was performed and confirmed the CT findings. Inferior petrosal sinus catheterization for ACTH in 4 patients confirmed excess pituitary ACTH secretion, correctly lateralizing the tumour in all cases. Cushing's disease was treated by transsphenoidal surgery alone in 6 patients and combined with pituitary irradiation in 3 patients. Of these 9 patients, 7 are cured and 2 are in remission. The patient with Nelson's syndrome is cured after total hypophysectomy. CONCLUSIONS: This series describes the clinical features, aetiologies and management of juvenile Cushing's syndrome. Investigation with low and high-dose dexamethasone suppression tests and hCRH test identified the aetiology in each case. Collaboration between paediatric and adult endocrine units together with an experienced neurosurgeon and a radiotherapist contributed to the successful therapeutic outcome of these patients.